Edistynyt analytiikka valmistavan teollisuuden organisaatiossa: tapaustutkimus - Haakana, Veikko (2025)
This thesis examines the applications of advanced analytics in a manufacturing organization. Initially, a literature review was conducted, followed by a qualitative, descriptive case study focusing on a large manufacturing company. The data was primarily collected through internal interviews within the company, but secondary data was also utilized. The main objective of the study was to determine the practical solutions the company has implemented in the field of advanced analytics. The study addressed both solutions intended for internal use and applications developed for the company's customers. For both internal and customer solutions, the study also explored how they support data-driven decision-making. Most of the applications were found to support data-driven approaches, but there are also complex applications that require decision-making based on human expertise and experience. The study also touches on big data and big data analytics, which falls under advanced analytics. The three Vs—volume, velocity, and variety—have long been considered the generally accepted characteristics of the definition. The big data literature also highlights other attributes, with value being identified as the most important based on this study. During the research, particularly through the interviews, it was noted that people have different perceptions of the term big data. Advanced analytics was found to be a better term than big data analytics, at least when discussing advanced analytics solutions in general, rather than just big data solutions.